Mandatory surveillance of bacteremia conducted by automated monitoring - Mølbak, Kåre; Andersen, Christian Østergaard; Dessau, Ram B.; Ellermann-Eriksen, Svend; Gubbels, Sophie; Jensen, Thøger Gorm; Knudsen, Jenny Dahl; Kristensen, Brian; Lützen, Lisbeth; Coia, John; Olesen, Bente Ruth Scharvik; Pinholt, Mette; et al. (Frontiers in Public Health, 2024)
Except for a few countries, comprehensive all-cause surveillance for bacteremia is not part of mandatory routine public health surveillance. We argue that time has come to include automated surveillance for bacteremia in the national surveillance systems, and explore diverse approaches and challenges in establishing bacteremia monitoring. Assessed against proposed criteria, surveillance for bacteremia should be given high priority. This is based on severity, burden of illness, health gains obtained by improved treatment and prevention, risk of outbreaks (including health care associated infections), the emergence of antimicrobial drug resistance as well as the changing epidemiology of bacteremia which is seen along with an aging population and advances in medical care. The establishment of comprehensive surveillance for bacteremia was until recently conceived as an insurmountable task. With computerized systems in clinical microbiology, surveillance by real-time data capture has become achievable. This calls for re-addressing the question of including bacteremia among the conditions under mandatory surveillance. Experiences from several countries, including Denmark, show that this is feasible. We propose enhanced international collaboration, legislative action, and funding to address the challenges and opportunities.